Pengaruh Perhatian Orang Tua dan Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Setingkat MTs (Indo-MathEdu Intellectuals Journal, 2025)
Learning motivation is crucial for students to achieve their educational goals. However, there are still many students who lack enthusiasm, are unfocused in their studies, and even do not have clear targets. Parental attention and a conducive school environment, as external factors, are two main aspects that support students' learning motivation and determine their future success. The aim of this research is to explore how parental attention and the school environment influence the learning motivation of students at the MTs level. This qualitative research uses a library research method by identifying patterns from relevant previous studies. The data sources of this research are related literature from books, journals, scientific articles, and official educational documents. The results of the study show that parental attention and involvement have a positive impact on students' learning motivation. The school environment, which includes aspects of teachers, physical conditions, and social interactions, provides positive support to enhance students' learning motivation. This research is expected to have an impact on schools and parents to improve students' learning motivation for the achievement of an optimal educational process.